Theoretical and Practical Issues That Are Relevant When Scaling Up hMSC Microcarrier Production Processes - Valentin Jossen; Cedric Schirmer; Dolman Mostafa Sindi; Regine Eibl; Matthias Kraume; Ralf Pörtner; Dieter Eibl (Hindawi Limited, 2016)
The potential of human mesenchymal stem cells (hMSCs) for allogeneic cell therapies has created a large amount of interest. However, this presupposes the availability of efficient scale-up procedures. Promising results have been reported for stirred bioreactors that operate with microcarriers. Recent publications focusing on microcarrier-based stirred bioreactors have demonstrated the successful use of Computational Fluid Dynamics (CFD) and suspension criteria (NS1u, NS1) for rapidly scaling up hMSC expansions from mL- to pilot scale. Nevertheless, one obstacle may be the formation of large microcarrier-cell-aggregates, which may result in mass transfer limitations and inhomogeneous distributions of stem cells in the culture broth. The dependence of microcarrier-cell-aggregate formation on impeller speed and shear stress levels was investigated for human adipose derived stromal/stem cells (hASCs) at the spinner scale by recording the Sauter mean diameter (d32) versus time. Cultivation at the suspension criteria provided d32 values between 0.2 and 0.7 mm, the highest cell densities (1.25 × 106 cells mL−1 hASCs), and the highest expansion factors (117.0 ± 4.7 on day 7), while maintaining the expression of specific surface markers. Furthermore, suitability of the suspension criterion NS1u was investigated for scaling up microcarrier-based processes in wave-mixed bioreactors for the first time.